Analysis of the Financial Ratios and Free Cash Flow of Telecommunication Subsector Companies - Rabbani, Usamah Jundi; Wijayanti, Risna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the financial performance of telecommunications subsector companies based on free cash flows and financial ratios to assess their financial health. Design/methodology/approach – This descriptive quantitative study uses secondary data from the annual financial statements of telecommunications subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Four companies were selected from a population of 22 using purposive sampling. Financial performance was evaluated through free cash flow analysis and liquidity, solvency, profitability, and activity ratios. Findings – The results indicate that the sampled companies exhibit both positive and negative free cash flows. Liquidity performance remains below industry standards, while solvency ratios exceed the recommended thresholds, indicating relatively high financial risk. Profitability performance varies across companies, with some achieving satisfactory results and others performing below industry standards. In addition, activity ratios generally remain below industry benchmarks, reflecting suboptimal operational efficiency. Originality/value – This study provides a comprehensive assessment of the financial health of Indonesia’s telecommunications subsector by integrating free cash flow analysis with financial ratio evaluation, offering useful insights for investors, managers, and other stakeholders.